Por mar, terra e ar: Dakar, Natal e as conexões transatlânticas (1880-1940) - Rubenilson B. Teixeira (Cahiers des Amériques Latines)
Natal, capital of the State of Rio Grande do Norte, Brazil, and Dakar, capital of Senegal, located respectively on extreme points of South America and West Africa, are settled in the shortest distance between the two continents, which are separated by the Atlantic. Historically speaking, both urban sites were strategic since the times of the great navigations, and remained important in the times of the modern development of communication systems brought about by the Industrial Revolution: steam navigation, the railroad, the aviation. This article deals with the historical similarities which can be detected in the relationship that both cities maintained with these communication systems and with their consequences in urban and territorial terms, between 1880 and 1940. The article also analyses the process of real approximation between the two cities in the period so established.